PI3K/Akt activity has variable cell-specific effects on expression of HIF target genes, CAIX and VEGF, in human cancer cell lines. - Shafee, Norazizah (Elsevier, 2009)
The phosphatidylinositol 3-kinase/Akt (PI3K) pathway regulates hypoxia-inducible factor (HIF) activity. Higher expression of HIF-1α and carbonic anhydrase IX (CAIX), a hypoxia-inducible gene, in HT10806TG fibrosarcoma cells (mutant N-ras allele), compared to derivative MCH603 cells (deleted mutant N-ras allele), correlated with increased PI3K activity. Constitutive activation of the PI3K pathway in MCH603/PI3Kact cells increased HIF-1α but, surprisingly, decreased CAIX levels. The cell-type specific inhibitory effect on CAIX was confirmed at the transcriptional level whereas epigenetic modifications of CA9 were ruled out. In summary, our data do not substantiate the generalization that PI3K upregulation leads to increased HIF activity.